'The fugitive': The figure of the judge in Coase's economics. Issue 2 (2nd October 2014) - BERTRAND, ELODIE
Abstract: 'The Problem of Social Cost' (Coase, 1960) asserts a normative role for the common law judge, that of taking into account the economic consequences of his decisions in allocating property rights. This position is often accused of inconsistency: Coase sees the figure of the judge as willing and able to improve economic efficiency, but criticises the actors of public intervention, particularly regulators, for being fallible, vulnerable to political pressures, and lacking information. I shall show that Coase's giving this role to the judge stems precisely from his criticism of public intervention. This means that his figure of the judge escapes the tenets of the theoretical system that first rendered it necessary. Various reasons could explain this difference of treatment as between the judge and the other figures of public intervention in Coase's system, but Coase makes too strong an opposition between common law on one side and regulatory and statutory law on the other, and leaves unexplained the motivation of judges.